An Improved Steganography Technique of LSB Substitution Method (International Journal of Engineering and Computer Science, 2015)
In this paper we have discussed the art and science of Steganography in general and proposed an algorithm which is the variant of LSB substitution method. It efficiently and effectively hides data with the help of a key in JPEG colored digital image. Security of hidden data is proportional to the length of key used. Proposed algorithm is capable to hide more data in cover image as compared to the many existing algorithm and require no pre-processing. Successful implementation of this algorithm opens the track for proposed algorithm to be used in data hiding and secure transmission